Perancangan Sistem Informasi Permohonan Penomoran Call Center Berbasis Web Menggunakan Metode Extreme Programming - Kiki Nurdiansyah; Kecitaan Harefa (CV. Multi Kreasi Media, 2023)
Today’s rapidly growing global telecommunications system has brought people into the world of information and communication technology (information society). The demand for improving public services that are good and satisfying the community is a need that must be met by the government. The purpose of this research is to develop a licensing and application information system and to establish a web-based Call Center numbering at the Telecommunications Directorate of the Ministry of Coommunication and Information Technology in order to provide better services. Developed using the Extreme Programming method and structured analysis modelling, this system was built using the PHP and MySQL programming language. The results of this study are the system can make it easier for applicants to get information, both the availability of numbers, submitting a call center application, numbering reports and monitoring the status of the application file. In addition employees can manage application data submitted by applicants quikly and transparently.